Covid-19 pandemic and social distancing in prisons - Frois, C. (Anthropology Today, 2020)
In the context of the Covid‐19 pandemic, how can the early release of prisoners, requested by the World Health Organization, members of civil society and non‐governmental organizations, be considered a ‘humane’ decision? In this article, the author examines the Portuguese context, discussing the ways that the urgency and fear of contagion highlighted, once more, the inability of prisons to cope with the needs of both those they confine and those they intend to protect.